Hybrid Model Based on User Tags and Textual Passwords and Pearsonian Type III Mixture Model - Rao, Pavan Gujjar Panduranga; Rao, Dr.P.Srinivasa; Devi, Dr. G. Lavanya (International Journal of Advanced Engineering Research and Science, 2020)
The latest advancements in Science and Technology, have witnessed radical changes in the banking system. Today most of the banks adopt the net banking facility and most of the users are also addicted to this system. Accordingly, most of the transactions are now online based and much emphasis is therefore needed to ensure the security of authenticating a person and validating the transaction. Many models are therefore proposed in the literature. Most of these are an alphanumeric based password schemes or biometric schemes or graphical password based schemes. Each of these models is proposed by underlying an advantage. The alphanumeric passwords are proposed, with the assumption that generating the password is easy and the generated password is unique, the biometric password schemes are proposed with the assumption that tampering a biometric is next to impossible. Graphical passwords are proposed with an option to the user so that he can select an image of his choice and then select some points which is called a click pattern, which is unique to every user.